99mTc-methylene diphosphonate SPECT/CT imaging of gout spondylitis: a case report. Issue 10 (October 2022) - Wang, Yan; Zha, Yan; She, Rongfeng; Sun, Gaofeng; Li, Shuang; Liu, Lin; Roberts, Neil; Li, Yaying
Single-photon emission computed tomography (SPECT)/computed tomography (CT) imaging of the gouty spine is rare. We describe a 66-year-old man who presented with pain and numbness in the right lower leg; he reported a 2-month history of intermittent low back pain. Imaging revealed neoplastic lesions of the spine, which were initially regarded as tumors. Thus, the patient underwent surgical removal of the lumbar lesion. However, the postoperative pathological diagnosis was gout spondylitis. In this report, we show multimodal images of advanced gout spondylitis. The metabolic information provided by SPECT/CT, combined with the microscopic changes in bone structure revealed by dual-source thin-layer CT and the anatomical localization information provided by magnetic resonance imaging, can help clinicians to more fully understand the pathophysiological mechanisms and imaging manifestations of gout from multiple perspectives, thereby reducing the rate of misdiagnosis.